2018
DOI: 10.1016/j.jvs.2018.03.394
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and effect of noncylindrical neck morphology on outcomes after endovascular aortic aneurysm repair in the Global Registry for Endovascular Aortic Treatment

Abstract: Noncylindrical neck morphology was more common in women and was associated with an increased use of aortic extender cuffs but did not increase the risk of intervention. Female gender and AAA diameter were associated with an increased need for reintervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…27,28 The Excluder device has been more commonly used in women than other devices given its applicability to a more complex anatomy. 20 Although women in our study had significantly smaller AAA diameters than men, they did possess a more hostile aortic anatomy, which may underlie the higher rates of overall and device related reintervention at 3 years. Therefore, perhaps, future guidelines should reflect the benefit of increased surveillance and follow-up of women beyond 3 years after EVAR to promptly identify and manage delayed adverse events.…”
Section: Discussionmentioning
confidence: 67%
“…27,28 The Excluder device has been more commonly used in women than other devices given its applicability to a more complex anatomy. 20 Although women in our study had significantly smaller AAA diameters than men, they did possess a more hostile aortic anatomy, which may underlie the higher rates of overall and device related reintervention at 3 years. Therefore, perhaps, future guidelines should reflect the benefit of increased surveillance and follow-up of women beyond 3 years after EVAR to promptly identify and manage delayed adverse events.…”
Section: Discussionmentioning
confidence: 67%
“…One study compared reverse tapered necks with standard necks, 40 one study compared reverse tapered necks with cylindrical necks, 41 and another study compared non-cylindrical necks with cylindrical necks. 42 No significant difference was reported between the cylindrical or standard and non-cylindrical or reversed tapered groups (three studies: OR 1.23, 95% CI .07 e 20.72), with moderate heterogeneity (c 2 p ¼ .16; I 2 ¼ 45%). The source of this statistical heterogeneity could not be explored due to the small number of included studies.…”
Section: Meta-analysis Of Neck Shapementioning
confidence: 93%
“…Mwipatayi 2013 [40] Schutze 2018 [42] Pitoulias 2017 [41] Total (random effects, 95% CI) statistically significant association between the presence of thrombus and calcification and type 1a endoleak or migration, 44,45 and one study found that mural neck thrombus was associated with type 1a endoleak and migration. 47 Notably, the overall evidence for these neck characteristics was low, due to the small number of included studies.…”
Section: Studiesmentioning
confidence: 99%
“…One study compared reverse tapered necks with standard necks, [61] one study com- pared reverse tapered necks with cylindrical necks, [62] and another study compared non-cylindrical necks with cylindrical necks. [63] No significant difference was reported between the cylindrical or standard and non-cylindrical or reversed tapered groups (three studies: OR 1.23, 95% CI .07 -20.72), with moderate heterogeneity (χ 2 p = .16; I 2 = 45%). The source of this statistical heterogeneity could not be explored due to the small number of included studies.…”
Section: Meta-analysis Of Neck Shapementioning
confidence: 91%
“…2. Nine studies compared proximal neck diameter, [40][41][42][43][44][45][46][47][48] two studies compared neck length, [49,50] 10 studies compared suprarenal and/or infrarenal angulation, [51][52][53][54][55][56][57][58][59][60] three studies compared neck shape, [61][62][63] and one study elaborated on the presence of thrombus. [64] No studies reported on calcification as a preoperativerative aortic neck characteristic relative to type 1a endoleak or migration.…”
Section: Description Of Studiesmentioning
confidence: 99%